Monetary Exchange Rate Model : Supportive Evidence from Nonlinear Testing Procedures - Venus, Khim-Sen Liew; Ahmad Zubaidi, Baharumshah; Muzafar Shah, Habibullah; Habshah, Midi (Universiti Malaysia Sabah (UMS), 2006)
Using nonlinear testing procedures relevant to the recent literature, this study provides evidence of nonlinear adjustment of nominal exchange rate towards monetary fundamentals in the context of ASEAN-5 countries. While it supports earlier findings supportive of monetary exchange rate model in this region using the linear testing procedures, this study provides insightful information in explaining why persistent misalignments between nominal exchange rate and monetary fundamentals are often observed in the sample data.